Association of BMI with pulmonary function, functional capacity, symptoms, and quality of life in ILD. (April 2022) - Schaeffer, Michele R.; Kumar, Divjot S.; Assayag, Deborah; Fisher, Jolene H.; Johannson, Kerri A.; Khalil, Nasreen; Kolb, Martin; Manganas, Hélène; Marcoux, Veronica S.; Guenette, Jordan A.; Ryerson, Christopher J.
Abstract: Obesity is a health epidemic associated with greater morbidity and mortality in the general population. Mass loading of the thorax from obesity leads to a restrictive pulmonary defect that reduces lung capacity in obese individuals without pulmonary disease, and may exacerbate the restrictive pulmonary physiology that is characteristic of interstitial lung disease (ILD). The purpose of this study was to test the association of body mass index (BMI) with pulmonary function, functional capacity, and patient-reported outcomes (dyspnea and quality of life) in patients with ILD. We analyzed 3169 patients with fibrotic ILD from the Canadian Registry for Pulmonary Fibrosis. Patients were subcategorized as underweight (BMI<18.5 kg/m 2 ), normal weight (18.5≤BMI<25), overweight (25≤BMI<30), obese I (30≤BMI<35), obese II (35≤BMI<40), and obese III (BMI>40). Analysis was performed using a linear regression with adjustment for common prognostic variables. Overweight and obese BMI categories were associated with worse pulmonary function, functional capacity, dyspnea, and quality of life compared to normal weight. This is likely a result of mass loading on the thorax, and we speculate that intentional weight-loss may improve lung function and functional capacity in obese patients with fibrotic ILD. The underweight BMI category was also associated with worse functional capacity compared to normal weight, which may reflect greater disease severity or the presence of other comorbidities. Future work should explore the clinical utility of BMI to improve patient outcomes. Highlights: Increasing BMI is associated with worse pulmonary function, functional capacity, dyspnea, and quality of life in ILD. Mass loading of the thorax in higher BMI categories could exacerbate the restrictive pulmonary defect characteristic of ILD. Intentional weight-loss in overweight and obese patients may improve pulmonary function in addition to functional capacity.